Relationship between Detection of Thermostable Direct Hemolysin Gene-Positive Vibrio parahaemolyticus from Environmental Samples and Food, and V. parahaemolytics Infection in a Particular District of Akita Prefecture, Japan - KONNO, Takayuki; SATIO, Shioko; SUZUKI, Noriyuki; YATSUYANAGI, Jun; HARATA, Seizaburo (Japanese Journal of Food Microbiology, 2005)
The relationship between the detection of thermostable direct hemolysin gene (tdh) -positive Vibrio parahemolyticus from environmental samples (estuarine water and estuarine mud) and Rock Oysters, and the emergence of V. parahaemolytics infection was investigated in a district of Akita prefecture in 2000 and 2001. A selective isolation method employing PCR for tdh, an immunomagnetic separation technique, and direct inoculation of tdh-positive enrichment broth onto a Wagatsuma agar, was used in the examination of the environmental samples and Rock Oysters. The number of cases V. parahaemolyticus infection decreased between 2000 and 2003, which was due to a decrease in the number of V. parahaemolyticus O3: K 6 (tdh+) patients. The period in which V. parahaemolyticus infection was observed in Honjyo city coincided with that in which Rock Oysters were retailed, and tdh-positive V. parahaemolyticus was isolated from both of the environmental samples and Rock Oysters obtained in that period, suggesting that Rock Oyster was one source of V. parahaemolyticus infection in Honjyo city. However, whether all Rock Oysters containing tdh-positive V. parahaemolyticus could cause human diarrhea was unclear, because the infectious dose of tdh-positive V. parahaemolyticus has not been established, and the number of tdh-positive V. parahaemolyticus in Rock Oysters was not measured. We propose from our findings that the temperature of Rock Oysters at retail stores should be kept low enough to prevent proliferation of tdh-positive V. parahaemolyticus, which should prevent V. parahaemolyticus infection. This is the first report showing a relationship between the detection of tdh-positive Vibrio parahemolyticus from the environmental and food samples, and the emergence of V. parahaemolytics infection in a particular district. In order to elucidate epidemiology of V. parahaemolyticus infection, further studies should be conducted in the different districts of Japan.